2012
DOI: 10.1109/titb.2011.2164088
|View full text |Cite
|
Sign up to set email alerts
|

Multisensor Data Fusion in an Integrated Tracking System for Endoscopic Surgery

Abstract: Surgical planning and navigation systems are vital for minimally invasive endoscopic surgeries but it is challenging to track the position and orientation of intrabody surgical instruments in these procedures. In order to address this problem, we propose a tracking system including multiple-sensor integration and data fusion. The proposed tracking approach is free of the constraints of line-of-sight, less subject to environmental distortion, and with higher update rate. By incorporating electromagnetic and ine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…Similar works are mainly reported by Ren in [11,19,20]. In his research, Ren combines a custom EMT subsystem designed in [32,33]—which contains a generator array bearing 48 coils and a receiving array bearing three coils—with a typical MARG sensor.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Similar works are mainly reported by Ren in [11,19,20]. In his research, Ren combines a custom EMT subsystem designed in [32,33]—which contains a generator array bearing 48 coils and a receiving array bearing three coils—with a typical MARG sensor.…”
Section: Resultssupporting
confidence: 55%
“…Commonly, an optical tracking [17,18] or inertial navigation system (INS) [19,20] can be adopted to assist EMT. However, restricted by the line-of-sight conditions [21], integrating EMT and INS becomes the most feasible solution for us, so in our solution, an INS is applied.…”
Section: Introductionmentioning
confidence: 99%
“…This error decreased significantly when the gyrosensor and accelerometer were used simultaneously. Use of accelerometer and gyrosensor in endoscopic guidance have been reported already [ 15 , 16 ]. Behrens and colleagues used accelerometer and gyrosensor for endoscope navigating system.…”
Section: Discussionmentioning
confidence: 99%
“…In the report, the mean error of the position measurement was between 1 and 4 degrees [ 15 ]. Ren, et al reported that accelerometer and gyrosensor can improve the accuracy of existing electromagnetic tracking system [ 16 ]. However, relatively little effort has been made to evaluate the clinical usefulness of this technology.…”
Section: Discussionmentioning
confidence: 99%
“…The possible clinical applications of the registration problem to be dealt with in this article are summarized as follows. (1) Pre-operative to intra-operative space alignment in CAS [2], [17], [23], [24]. (2) Statistical shape modelling (SSM).…”
Section: Introductionmentioning
confidence: 99%